A Indústria Cinematográfica no Brasil: análise da produção, distribuição e exibição de filmes nacionais no período 1995-2009 - Michel, Rodrigo Cavalcante (2011)
The evolution of the productive chain in Brazil‟s movie industry, was and still is restrained by some governmental policies that drive it forward. Since the beginning of the nineties, movie productions take a new and accelerated dynamics, reinforcing the role of the state as a supporter. The purpose of the present paper is to analyze the dynamism of the movie industry in Brazil, looking into the productive sectors, distributors and exhibitors of its movies between the years 1995 and 2009, also highlighting the governmental policies carried on throughout all these years. Among the results acquired during this research, despite the restoration of the productive dynamics, it is acknowledged a reduction on the productive chain and its sectors, showing difficulties when entering into the movie market. This way, it becomes clear the need of governmental policies that reach all the productive chain, so that the national movie industry could take a wider market share in the country.